2020
DOI: 10.13106/jafeb.2020.vol7.no11.1021
|View full text |Cite
|
Sign up to set email alerts
|

Training-Effectiveness and Team-Performance in Public Organization

Abstract: This study aims to invest in empirical relationships in a model that becomes the process of Team-Performance due to participation in practical training through causality between Training Effectiveness variables, soft-skill competence, Employee-Creativity, and team performance. This study uses a quantitative approach. The analytical tool used is structural equation modeling (SEM) using AMOS version 23 software. Accidental sampling technique is used to collect the sample. As many as 202 respondents filled up a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
(50 reference statements)
0
17
0
3
Order By: Relevance
“…Owned expertise will give rise to awareness, skills, and conduct (Hutapea and Thoha, 2008). Previous research findings supporting this partnership include Umar et al (2020), Diny Ayuningtyas (2012), Ubaidillah (2018), Ai Nurasiah & Mala Tri Marliana (2018), and Dina Amaluis (2014) concluded that competence is impaired by training effectiveness. Hypothesis 1 may, thus, be rendered as follows: H1: The effectiveness of training has a positive and vital impact on the production of skills, the higher the effectiveness of training can enhance the skills of workers at the Polres of Soppeng Regency Careers are all occupations or positions that are supervised or retained during the professional life of a person.…”
Section: Literature Reviewmentioning
confidence: 79%
See 2 more Smart Citations
“…Owned expertise will give rise to awareness, skills, and conduct (Hutapea and Thoha, 2008). Previous research findings supporting this partnership include Umar et al (2020), Diny Ayuningtyas (2012), Ubaidillah (2018), Ai Nurasiah & Mala Tri Marliana (2018), and Dina Amaluis (2014) concluded that competence is impaired by training effectiveness. Hypothesis 1 may, thus, be rendered as follows: H1: The effectiveness of training has a positive and vital impact on the production of skills, the higher the effectiveness of training can enhance the skills of workers at the Polres of Soppeng Regency Careers are all occupations or positions that are supervised or retained during the professional life of a person.…”
Section: Literature Reviewmentioning
confidence: 79%
“…The creation of human capital is an undertaking that any organization must carry out, ensuring that their expertise, talents, and abilities align with the guidance of the job they are doing (Muhajji et al, 2016;Umar et al, 2020). With this development, it is hoped that doing a better job can be strengthened and resolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education and training can benefit from enhancing workers' efficiency, education, and practice by improving employees' skills and attitudes to better respond to their job environment (Tamsah et al, 2020;A Umar et al, 2020). The points put forward by Sumarsono (2009) on education and training, where education and training are one of the significant factors in human resources development (HR).…”
Section: Introductionmentioning
confidence: 99%
“…Employee motivation is one of the elements that must be addressed when providing reliable public facilities for the city. Quality human capital with a well-disciplined mindset is required to empower public servants (Rahawarin et al, 2020;Sawitri et al, 2019;A Umar et al, 2020). Employee discipline is closely tied to the advancement of professional public services (Rahawarin et al, 2020;Akmal Umar, Hasbi, et al, 2019;Yusriadi Yusriadi & Misnawati, 2017).…”
Section: Introductionmentioning
confidence: 99%